2015
DOI: 10.1002/cbic.201402716
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase Inhibition by Heterotrimeric Triple‐Helical Peptide Transition State Analogues

Abstract: Matrix metalloproteinases (MMPs) have been implicated in numerous pathologies. An overall lack of selectivity has rendered active site targeted MMP inhibitors problematic. The present study describes MMP inhibitors that function by binding both secondary binding sites (exosites) and the active site. Heterotrimeric triple-helical peptide transition-state analog inhibitors (THPIs) were assembled utilizing click chemistry. Three different heterotrimers were constructed, allowing for the inhibitory phosphinate moi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

6
4

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…Inhibition of MMPs by RTD-1 was performed as described [ 24 ], incubating each enzyme with 0–100 μg/ml of RTD-1. IC 50 values were calculated by GraphPad Prism 5.01 (GraphPad Software, San Diego, CA) utilizing a non-linear curve fit of log [inhibitor] versus response with variable slope.…”
Section: Methodsmentioning
confidence: 99%
“…Inhibition of MMPs by RTD-1 was performed as described [ 24 ], incubating each enzyme with 0–100 μg/ml of RTD-1. IC 50 values were calculated by GraphPad Prism 5.01 (GraphPad Software, San Diego, CA) utilizing a non-linear curve fit of log [inhibitor] versus response with variable slope.…”
Section: Methodsmentioning
confidence: 99%
“…Phosphinic peptides offer the possibility of interacting with both the primed and unprimed sides of the MMP active site cleft [43]. We have reported that phosphinic triple-helical peptides (THPs) behave as effective transition state analog inhibitors of collagenolytic MMPs [67,149,150,151,152]. These triple-helical peptide inhibitors (THPIs) have proven effective in mouse models of multiple sclerosis, sepsis, and myocardial infarction [67,153].…”
Section: Development Of Improved Mmp Inhibitorsmentioning
confidence: 99%
“…Phosphinic dipeptides contain a hydrolytically stable, tetrahedral phosphinic moiety that mimics the tetrahedral intermediate formed during enzymatic hydrolysis. Previously, we reported that phosphinic triple-helical peptides (THPs) behave as effective transition state analog inhibitors of collagenolytic MMPs 12,14,15. More specifically, two homotrimeric triple-helical peptide inhibitors (THPIs), C 6 -(Gly-Pro-Hyp) 4 -Gly-Pro-Pro-Gly Ψ {PO 2 H-CH 2 }Val-Val-Gly-Glu-Gln-Gly-Glu-Gln-Gly-Pro-Pro-(Gly-Pro-Hyp) 4 -NH 2 [designated C 6 - α 1(V)Gly Ψ {PO 2 H-CH 2 }Val THPI] and (Gly-Pro-Hyp) 4 -Gly-mep-Flp-Gly-Pro-Gln-Gly Ψ {PO 2 H-CH 2 }Leu-Ala-Gly-Gln-Arg-Gly-Ile-Arg-Gly-mep-Flp-(Gly-Pro-Hyp) 4 -Tyr-NH 2 [designated α 1(I-III)Gly Ψ {PO 2 H-CH 2 }Leu THPI], were shown to inhibit MMPs in the low nanomolar range 12,14.…”
Section: Introductionmentioning
confidence: 99%